(3GdBKGQ GdCefjI dXGgQI GdJcajQ hGdEQgGH (B/s - (3GdLMfj, Ydj Hf aGjRs ((3GdQjGV (B:s (3OGQ eedcI fLO ddfTQ hGdJhRjY,s, 2014)
(3dG Tc Cf XGgQI GdEQgGH JSJOYj GdeYGdLI GdUQjMI hGdhGVMI, dGSjeG Cf GdMaGX Ydi GdCef hGdGSJbQGQ eSDhdjI JVGefjI eTJQcI Hjf cGaI CaQGO GdeLJeY, aGdcd eSDhd Yf JhajQ GdCef, haj GdhbJ faSg eSDhd Yf ecGaMI cd GdXhGgQ GdeGSI HGdCef hGdGSJbQGQ hGdJfejI, hefgG XGgQI GdEQgGH GdJj JcGO JTZd LejY Ohd GdYGde aj GdhbJ GdMGVQ, gPg GdXGgQI GdJj JYcS acQkG eJWQakG efMQakG jSJfO Edi CacGQ XdGejI hjfWdb ef aJGhi eVddI NGQLI YeG CLeY Ydjg YdeGA GdESdGe GdKbGJ, ef gfG aEf Jdc GdaFGJ GdeJWQaI EfeG JJMQc VO faSgG hOjfgG hChWGfgG hVO GdYGde HCSQI(B.s
(3TQGA eYQV GdQjGV GdOhdj ddcJGH (B2014.s
(3HHdjhLQGajI (B: (3U(B. 167-172.s
Keywords: (3GdEQgGH GdOhdjs; (3GdJcajQs; (3GdEQgGHs -- (3ebGheIs; (3GdJacc GdGLJeGYjs; (3UQGY Gdbjes; (3fXQjI GdaQUIs; (3GdfXQjI GdGfMQGajIs; (3GdHGKhdhLjG GdGLJeGYjIs; (3GdESdGe hGdEQgGHs; (3GdhSWjIs; (3MeGjI GdhSWjIs; (3GdCef hGdGSJbQGQs; (3GdESdGe hGdCSQIs; (3gQhH GdCWaGd s; (3GdJYGhf GdOhdjs; (3GdCef GdCSQjs; (3MeGjI GdCSQI s; (3EOGQI GdCReGJ s; (3GdQbGHI GdEYdGejIs; (3GdEYdGe GdCefj s; (3GdCef GdLeGYjs; (3GdYdGbGJ GdOhdjIs; (3CSdMI GdOeGQ GdTGeds; (3GdJYGhf GdCefj GdOhdjs